Emerging Developments Regarding Nanocellulose-Based Membrane Filtration Material against Microbes - Norrrahim, Mohd Nor Faiz; Mohd Kasim, Noor Azilah; Knight, Victor Feizal; Ong, Keat Khim; Mohd Noor, Siti Aminah; Abdul Halim, Norhana; Ahmad Shah, Noor Aisyah; Jamal, Siti Hasnawati; Janudin, Nurjahirah; Misenan, Muhammad Syukri Mohamad; Ahmad, Muhammad Zamharir; Yaacob, Mohd Hanif; et al. (MDPI, 2021)
The wide availability and diversity of dangerous microbes poses a considerable problem for health professionals and in the development of new healthcare products. Numerous studies have been conducted to develop membrane filters that have antibacterial properties to solve this problem. Without proper protective filter equipment, healthcare providers, essential workers, and the general public are exposed to the risk of infection. A combination of nanotechnology and biosorption is expected to offer a new and greener approach to improve the usefulness of polysaccharides as an advanced membrane filtration material. Nanocellulose is among the emerging materials of this century and several studies have proven its use in filtering microbes. Its high specific surface area enables the adsorption of various microbial species, and its innate porosity can separate various molecules and retain microbial objects. Besides this, the presence of an abundant OH groups in nanocellulose grants its unique surface modification, which can increase its filtration efficiency through the formation of affinity interactions toward microbes. In this review, an update of the most relevant uses of nanocellulose as a new class of membrane filters against microbes is outlined. Key advancements in surface modifications of nanocellulose to enhance its rejection mechanism are also critically discussed. To the best of our knowledge, this is the first review focusing on the development of nanocellulose as a membrane filter against microbes.
Keywords: nanocellulose; membrane filter; microbes; surface functionalization; CELLULOSE NANOCRYSTALS; WATER-PURIFICATION; SUPERHEATED STEAM; VIRUS; REMOVAL; FILTER; PAPER; PRETREATMENT; NANOFIBRILS; BIOREACTORS; Polymer Science